2020
DOI: 10.23960/jbekh.v7i1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Grasshoppers in Liwa Botanical Garden Based on Time Capture

Abstract: Grasshopper is one of the diurnal cosmopolitan insect, the existence of grasshoppers is very influential for some other animal populations such as birds. It is still lack of information of diversity, distribution, population, and other basic biological aspects of grasshoppers at Kebun Raya Liwa (KRL). To monitor biodiversity, it is necessary to provide informations about  the number of individuals, their functions, and roles in the habitat and ecosystem. Therefore it is necessary to conduct  the research of  t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Jaring serangga diayunkan ke kanan dan ke kiri dengan konsisten sebanyak sepuluh kali ayunan disepanjang jalur yang telah ditentukan [15]. Waktu pengambilan data dilakukan pada pagi hari pukul 08.00 -10.00 WIB dan sore hari pukul 14.00 -16.00 WIB [16]. Setiap spesimen belalang yang sudah tertangkap kemudian dibedakan berdasarkan karakteristik morfologinya (warna, ukuran tubuh, femur belakang, bentuk kepala).…”
Section: Waktu Dan Tempat Penelitianunclassified
“…Jaring serangga diayunkan ke kanan dan ke kiri dengan konsisten sebanyak sepuluh kali ayunan disepanjang jalur yang telah ditentukan [15]. Waktu pengambilan data dilakukan pada pagi hari pukul 08.00 -10.00 WIB dan sore hari pukul 14.00 -16.00 WIB [16]. Setiap spesimen belalang yang sudah tertangkap kemudian dibedakan berdasarkan karakteristik morfologinya (warna, ukuran tubuh, femur belakang, bentuk kepala).…”
Section: Waktu Dan Tempat Penelitianunclassified
“…However, the research results show that the existence of species found is very small, usually only numbering dozens. It is evident from the results of research conducted by [4][5][6] East Lombok Regency is one of the Level II Regions or districts in West Nusa Tenggara, Indonesia. The capital city of East Lombok is in the Selong district.…”
Section: Introductionmentioning
confidence: 99%
“…The order Orthothera can be found in almost all terrestrial ecosystems and in Indonesia. Grasshoppers are distributed in almost all parts of Indonesia such as Java, Sumatra, Kalimantan, Sulawesi, and other islands that have environmental or ecosystem types including forests, shrubs / shrubs, residential areas, agricultural land, etc [3,4].…”
Section: Introductionmentioning
confidence: 99%